2014
DOI: 10.1002/jcph.326
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics, and safety of pasireotide LAR in patients with acromegaly: A randomized, multicenter, open‐label, phase I study

Abstract: Pasireotide (SOM230), a multireceptor-targeted somatostatin analogue, has exhibited favorable safety/tolerability in several clinical studies. A long-acting-release (LAR) formulation of pasireotide may offer advantages over the subcutaneous formulation. This randomized, open-label, Phase I study evaluated the safety, PK, and PD of pasireotide LAR 20, 40, or 60 mg/month in patients with acromegaly. Safety assessments and blood samples for PK and PD were taken at designated time points. Thirty-five patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Both pasireotide (Petersenn et al 2014a) and pasireotide LAR (Petersenn et al 2014b) appear promising as medical agents with antisecretory and antitumoral effect. A comparison between pasireotide LAR 40 mg/28 days and OCT-LAR 20 mg/28 days revealed that biochemical control (GH !2.5 mg/l and normal IGF1) after 12 months was achieved in significantly more cases treated with pasireotide LAR than with OCT-LAR (31% vs 19%).…”
Section: Medical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Both pasireotide (Petersenn et al 2014a) and pasireotide LAR (Petersenn et al 2014b) appear promising as medical agents with antisecretory and antitumoral effect. A comparison between pasireotide LAR 40 mg/28 days and OCT-LAR 20 mg/28 days revealed that biochemical control (GH !2.5 mg/l and normal IGF1) after 12 months was achieved in significantly more cases treated with pasireotide LAR than with OCT-LAR (31% vs 19%).…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Rare complications of SRS are cranial nerves deficits, headache, radiation necrosis, carotid artery stenosis, and trigeminal neuralgia (Beauregard et al 2003, Stapleton et al 2010. The risk of visual complications limits the use of SRS to lesions more than 3 mm away from the optic structures (Petrovich et al 2003). To date, if RT is indicated, stereotactic methods should be applied, unless the tumor remnant is large or close to the optic apparatus (Katznelson et al 2014).…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Following a washout period if prior medical therapy had been used, pasireotide was administered once every month for 3 months. At day 91, 51 % of patients across all groups had mean GH levels of B2.5 lg/L (compared with 11 % at baseline), and over the 3-month period, mean GH levels had decreased by 67, 60 and 63 % in groups receiving pasireotide 20, 40 or 60 mg, respectively [12]. At month 3, mean serum IGF-1 levels had decreased to below the upper limit of normal (ULN) in 57 % of patients, and decreases from baseline of 40, 51 and 50 % were observed in each group, respectively.…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 92%
“…GH and IGF-1 levels were rapidly suppressed following the first intramuscular injection of pasireotide 20, 40 or 60 mg, and suppression was maintained throughout treatment in a randomised, phase I study in patients with acromegaly (n = 35) [12]. Following a washout period if prior medical therapy had been used, pasireotide was administered once every month for 3 months.…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation